TYPES OF ENGLISH LANGUAGE TEST - Nike Angraini (Universitas Indo Global Mandiri, 2016)
In this globalization era, English is very prominent for many people all over the world starts from students in elementary school till students in university level. The students are expected to master English language both in oral and written communication. If the students are able to master English, they can use it to interact and socialize with people who are not only from Indonesia but also from other countries. Therefore, to see whether or not the students succeed inmastering English, the test must be administered. This articleaims to discuss miscellaneous of tests which can be used in teaching and learning environment. Some conclusions and suggestions are made to ensure both the teacher and students will gain benefits from these types of English language test.Keyword : types, English language, test